Single-cell RNA sequencing of circulating immune cells supports inhibition of TNFAIP3 and NFKBIA translation as psoriatic arthritis biomarkers - Garrido, Ameth N.; Machhar, Rohan; Cruz-Correa, Omar F.; Ganatra, Darshini; Crome, Sarah Q.; Wither, Joan; Jurisica, Igor; Gladman, Dafna D. (Frontiers in Immunology, 2025)
ObjectiveTo identify biomarkers that distinguish psoriatic arthritis (PsA) from cutaneous psoriasis without arthritis (PsC) and healthy controls (HC) using single cell RNA sequencing (scRNA-seq).MethodPeripheral blood mononuclear cell samples from three patients with PsA fulfilling CASPAR criteria, three patients with PsC and two HC were profiled using scRNA-seq. Differentially expressed genes (DEGs) identified through scRNA-seq were validated on classical monocytes, and CD4+ and CD8+ T cell subsets derived from an independent cohort of patients using the NanoString nCounter® platform. Protein expression was measured in CD4+ and CD8+ T cells by immunoblotting.ResultsA total of 18 immune cell population clusters were identified. Across 18 cell clusters, we identified 234 DEGs. NFKBIA and TNFAIP3 were overexpressed in PsA vs HC and PsC patients. Immunoblotting of the proteins encoded in these genes (IκBα and A20, respectively) showed higher levels in PsA CD4+ T cells compared to HC. Conversely, lower levels were observed in PsA CD8+ T cell lysates compared to HC for both proteins.ConclusionThese results suggest that translation of TNFAIP3 and NFKBIA may be inhibited in PsA CD8+ T cells. This study provides insight into the cellular heterogeneity of PsA, showing that non-cell type specific expression of genes associated with the disease can be dysregulated through different mechanisms in distinct cell types.